Effectiveness of Citra Education in Universiti Kebangsaan Malaysia from Students’ Perspective - Muslim, Nazri; Din, Wardah Mustafa; Khaidzir, Mohd Fadhli Shah; Arham, Ahmad Firdhaus; Alias, Jamsari; Mat, Norazila (Journal of Posthumanism, 2025)
Higher education in Malaysia has evolved rapidly and become more stable over the decades. This situation demands a shift from the standard approach in higher education to a more flexible one. The development of the higher education’s curriculum should also focus on the education system that enables student to understand shared values and the sharing of experience as well as aspiration. As a multi-cultural country, Malaysia develops its higher education curriculum in a multicultural context as it is vital to instill values of patriotism and unity to help students grasp national goals, be proficient in the national language, and grow into globally minded individuals with a proud Malaysian. Universiti Kebangsaan Malaysia (UKM) address this through the Citra Education with a wider and more compact learning approach to develop students with great character and broad knowledge across multi disciplines. The Citra Education is compulsory to all students as a requirement for graduation. This article explores the effectiveness of Citra Education from the students’ perspective via a self-administered questionnaire (n=297). Generally, the majority of the UKM students agreed that Citra Education is effective in achieving the intended objective.